Administração crônica de flúor: efeitos no metabolismo e na reprodução de ovinos - Filappi, Andreane Rosa (2008)
Mineral nutrition has a major effect upon animal productivity. Recently, the use different sources of phosphorus in supplements have been discussed, these have higher fluoride (F) content than traditional sources. Although F is considered an essential element, most biological interest is turned to its toxic effects. Therefore, the objective of the present study was to evaluate F metabolism, its effects upon liver function, seminal quality, including oxidative profile, and, histomorphometric variables of the reproductive system of ram lambs chronically exposed to sodium fluoride (NaF). Twelve 5 month old ram lambs, maintained on alfalfa hay (3% BW) and nonfluorinated water ad libitum were divided in 2 groups: Control, which received 5g NaCl/animal + 0.2 mg I/Kg DM daily; and treated that received the same as control plus NaF (4.7 mg F/Kg BW). Treatments were given by gavage, daily, for 150 days. Blood, urine, fecal and ejaculate samples were collected. After 150 days of treatment animals were euthanized and the pineal gland, testicle, tail of the epididymus, vas deferens, and samples of bone and liver were collected. Serum, urine, and bone values of F were higher in treated animals. No differences were observed in whole pineal F content. Serum protein, albumin, and cholesterol concentrations were not different between groups, also, no differences were detected in the plasma AST and GGT activity. No histological changes observed in the liver, testicle, tail of the epididymus, and vas deferens. In seminal samples, no differences were observed in motility, viability, and spermatic morphology, concentration of reduced glutathione, and zinc. The concentration of thiobarbituric acid reactive substances (TBARS) and copper were lower in F treated animals than in controls. In conclusion, chronic F treatment leads to F deposition in bones. The capacity of lambs to deal with F excess is different than what is reported in other species. Chronic fluorine intake in lambs does not lead to structural alterations of the reproductive system, nor affects seminal quality. However, sub clinical alterations in the seminal oxidative profile can occur and lead to impairment of fertility.